(untitled) (The Journal of Plant Protection Sciences, 2023)
Ber (Zizyphus mauritiana Lamk - Rhamna ceae) is one of the important fruit crops of arid and semi arid zones of the world. In India though it is a minor fruit but recently the ber become an important cash crop in some areas and its acreage and production are increased. Due to rapid spread of commercial cultiva tion, the crop is also affected by different bi otic and abiotic factors including pathogens causing many serious diseases. Not much at tention to the diseases of ber has been given so far and remained under-estimated the prob lems. The ber, a tropical fruit crop is prevalent in arid and semi-arid region of the world. The crop considered as minor fruit in this country on the basis of its production in restricted area, popularity and awareness although it is a very important crop and contributes a good share of economy in many localities. Several biotic and abiotic stresses have been responsi ble for causing diseases, related to loss of crop. As the importance of the crop generally continue in a locality or a particular state thus it overlooks the national importance particu larly researches on protection technology, leading to limited knowledge for management of different diseases both in pre-harvest as well as post-harvest stage. Ber is affected by many serious diseases like powdery mildew, sooty mold, leaf spots (Alternaria, Cerco spora, Septoria, Cladosporium, Pestalo tiopsis etc.) and rust among the fungal infec tions and witches broom caused by MLOs as reported by Jamader et al. (3). Seven diseases on ber were identified by Yuan et al. (7) in China mostly grown in the southern provinces of the country and also grown in India. While many diseases originated in the orchards, fruit rot may initiates from the filed and may ex press in storage due to lack of proper handling and storage conditions. The amount of loss caused by fruit diseases is tremendous and has not yet been documented properly and thus adoption of suitable remedial measure is needed. The present investigation was carried during 2010-11 to identify the diseases preva lent in ber and also to find out seasonal varia tion of different diseases.